Analysis of cheating in human patterns using Stockfish suggestions - Santos, João Batista Andrade; Ávila, Emanuel; Oliveira, Caio; Gomes, Vitor Manuel; Maia, José Gilvan R.; Franco, Artur (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2024)
Online games are growing, and cheating is becoming more common. Chess, considered a sport by many, often faces cheating in tournaments. The website chess.com daily blocks hundreds of accounts accused of cheating, often using engines like Stockfish. This study analyzes human patterns in thousands of matches using Stockfish to identify cheating. Results show that Stockfish analysis helps identify cheating by comparing players' Elo ratings and move sequences. However, this method alone is insufficient for definitive accusations, necessitating the combination with other robust methods to increase the accuracy of accusations, providing a more comprehensive approach to combating cheating.